PENGARUH E-COMMERCE DAN PENGGUNAAN SISTEM INFORMASI AKUNTANSI TERHADAP EFEKTIVITAS KINERJA UMKM DI KOTA BATAM - Desyanti Desyanti; Handra Tipa (LPPM Universitas Putera Batam, 2025)
Micro, Small, and Medium Enterprises (MSMEs) operating in Batam are the focal point of this study, which aims to examine how the adoption of information technology for accounting activities and online trading impacts their efficiency and productivity. Although MSMEs contribute significantly to strengthening the regional economy, they still face various challenges related to optimal management. Many MSME actors believe that more accurate financial decision-making and greater operational efficiency can be achieved through the use of digital technologies such as accounting information systems and e-commerce. This research involved 135 MSME respondents in the culinary sector located in Bengkong District, employing an associative quantitative approach. Data processing in this study was conducted using multiple linear regression analysis with the aid of SPSS version 25. The results indicate that both accounting information systems and e-commerce have a significant effect on MSME performance, although the magnitude of their influence differs, both individually and jointly. The obtained Adjusted R² value of 0.455 suggests that these two variables can explain 45.5% of the variation in MSME performance effectiveness. These findings underscore the importance of digitalization and well-structured financial recording in supporting the sustainability and competitiveness of MSMEs in today’s digital market era Keywords: E-Commerce, Accounting Information System, Performance Effectiveness, MSMEs, Batam.